Ketidakselarasan dalam Wewenang untuk Menyelesaikan Sengketa Pemilu Lokal Pasca-Keputusan Mahkamah Konstitusional - La Ewo, Jefriansyah (Institut Agama Islam (IAIN) Kendari, 2026)
This study analyzes the authority to resolve local election (Pilkada) result disputes in Indonesia, which have been subject to frequent regulatory changes and constitutional reinterpretations. The main issue is how judicial authority over Pilkada disputes has evolved and what system best ensures legal certainty and the rule of law. The study highlights a normative conflict between Law No. 10 of 2016 and Constitutional Court Decision No. 85/PUU-XX/2022 and offers a model for a constitutionally consistent and coherent legal structure. This research employs a normative legal method, drawing on legislative, conceptual, and case law approaches through a literature review of legal materials. The analysis directly examines the relationship between legal norms and constitutional practices in Pilkada dispute resolution. Findings show that shifting authority between the Supreme Court and Constitutional Court has caused legal uncertainty, regulatory conflict, and weakened protection of Pilkada participants’ rights. Constitutional Court Decision No. 85/PUU-XX/2022 establishes the Constitutional Court as the permanent body for Pilkada disputes. This research underscores the need for normative harmonization and stronger legal and political policies to create a stable, fair, and certain dispute-resolution system for Pilkada.